Designing Multimodal Literacy Instruction Based on the TPACK Model for Teachers at SD Negeri 149 Palembang - Hesti Wahyuni Anggraini; Machdalena Vianty; Ismail Petrus; Zuraida; Amrullah; Muhammad Yazir; Tita Ratna Wulan Dari; Yentri Anggeraini; Lianasari; Firma Pradesta Amanah (CV. Era Digital Nusantara, 2026)
Strong literacy skills have a significant impact on the mastery of other areas, including numeracy. Although numeracy itself does not directly contribute to the core definition of multimodal literacy, numerical concepts can be taught using a multimodal approach through the use of visual, audio, and kinesthetic modes. Thus, multimodal literacy not only supports the development of language competencies, but can also enrich cross-disciplinary learning strategies. For multimodal learning to be implemented optimally, teachers need to master TPACK, which enables them to design meaningful learning experiences by effectively utilizing technology. This community service activity aims at providing solutions to these problems through training and mentoring for teachers as SD Negeri 149 Palembang in designing and implementing TPACK-based multimodal literacy, the basic principles of TPACK, and practical applications in developing lesson plans that integrate technology and multimodality. This activity was conducted from October 2025 to November 2025, at SD Negeri 149 Palembang, attended by 23 teachers. The implementation methods included four stages, namely identification of teachers’ needs and potential through observations and interviews; presentation on the theory and practice of multimodal literacy and TPACK; workshop on designing TPACK-based and multimodal learning; and the implementation and evaluation of classroom activities. Supported by simple technology applications, such as Canva and other interactive applications, the activity resulted on the knowledge about how to meaningfully integrate technology with pedagogical approaches and content to create rich and engaging learning experiences for students. The use of Topworksheets was one alternative to choose.